LITERARY WORKS IN THE AMERICAN CULTURE - Sudiran, Sudiran (Jurnal Bestari, 1997)
The novel entitled "Uncle Tom's Cabin", for instance, was firstly published in 1852 and sold 7 milions copies. American newspaper is started when Boston News-Letter became first regularly published American newspaper in 1704. In 1791, Bill of Rights was ratified in America in which government protected press from censorship. It was proved by First Amendment. Moreover, American megazine was firstly published in 1741. In 1821, "saturday Evening Post" was published. Then, first megazine boom occured during 1865 to 1900.